Basic principles and applications of photoelectrochemical reactions - Branimir N. Grgur (Zaštita Materijala)
The paper discusses the basic principles of photoelectrochemistry and photo electrochemical reactions. Considered the application photoelectrochemicl cells in the conversion of the sun iradiation energy into electricity. In addition, the working principle of new types of fuel photoelectrochemical fuel cells that can simultaneously produce electricity and perform degradation of polluting organic substances is discussed.